Factors predicting the development of urethral stricture after bipolar transurethral resection of the prostate - Afandiyev,Faraj (2022)
SUMMARY OBJECTIVE: We aimed to investigate the rate of urethral stricture development, predictor factors, and the reliability following bipolar transurethral resection of the prostate. METHODS: A total of 124 patients participated in this study. Patient data were retrospectively reviewed. The patients were divided into group 1 (those who developed urethral stricture) and group 2 (those who did not develop urethral stricture). Annual checkups were performed after the postoperative months 1 and 6. The patients were checked by uroflowmetry + post-voiding residue and international index of erectile function. We evaluated the complications that developed during the perioperative period according to the Clavien system. RESULTS: Urethral stricture developed in 10.5% (13/124) of the patients. It was found that patients who underwent transurethral resection of the prostate for the second time (p=0.007), patients with a preoperative catheter or history of catheter insertion (p=0.009), patients with high preoperative median white blood cell (103) counts (p=0.013), and patients with long postoperative catheterization time had a higher rate of urethral stricture after bipolar transurethral resection of the prostate (p=0.046). No grade 4 and grade 5 complications were observed according to the Clavien system in patients. CONCLUSION: Factors such as second transurethral resection of the prostate surgery, history of preoperative catheter insertion, high postoperative white blood cell count, and long postoperative catheterization time increase the risk of urethral stricture after bipolar transurethral resection of the prostate.